The evolution of ultrathin polyamide film during molecular layer-by-layer deposition. (January 2023) - Liu, Yingying; Wu, Haowen; Zhang, Haifeng; Wang, Jixiao; Wang, Zhi
Abstract: The physicochemical properties (surface morphology, roughness, average molecular spacing, wettability, element content, and crosslinking degree) of molecular layer-by-layer (mLbL) PA films, which could be used in reverse osmosis (RO) application, based on m -phenylenediamine (MPD) and trimesoyl chloride (TMC) under low (1-15) deposition cycles are investigated in detail. In this work, the mLbL films are investigated with respect to MPD/TMC ratio, and the number of deposition cycles. Results show that the film grows faster with higher MPD/TMC ratio. For the same deposition cycle, the film has lower average molecular spacing, is better crosslinked and denser under higher MPD/TMC ratio. During deposition process, the monomers distribute unevenly, inducing the nodules structure on the film surface. Under lower deposition cycles, the average molecular spacing of the film is not homogeneous and the film is worse crosslinked; as the deposition process repeating, the film develops to be uniform, dense, and highly crosslinked, accompanying the growth of nodules and the filling of the "valley" between the nodules by monomers. Besides, the physicochemical properties of the most complete mLbL PA film prepared in this work and the interfacial polymerization (IP) membranes are compared to strength the understanding of IP. Results show that the rough structure of IP-PA films can be attributed to the uncontrolled aqueous monomer diffusion and the interface instability of reaction zone in IP; controlling the uniform distribution of monomers is conducive to preparing homogeneous PA membranes with possible high performance. In short, this study investigated the evolution of the mLbL PA film during the initial deposition stage and may inspire the development of advanced mLbL RO membranes. Highlights: The evolution of polyamide (PA) film in molecular layer-by-layer (mLbL) was investigated. High monomer ratio could facilitate the growth of PA mLbL film, produce a developed PA film. As the deposition process repeating, the film develops to be uniform, dense, and highly crosslinked. The film formation characteristics in the interfacial polymerization (IP) was speculated by comparing the IP and mLbL.